2018
DOI: 10.1021/acs.jpcc.8b05582
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Optical Properties and Excited-State Dynamics by Linearizing Cyclic Paraphenylene Chromophores

Abstract: Cyclic and bent conjugated molecular systems have tunable optical, structural, and dynamical features that differentiate them from their linear counterparts. Examples of such systems are [n]­cycloparaphenylenes (CPPs), which consist of nanorings composed of n para-linked benzene units. Circular geometry and tunability of π-orbital overlaps and bending strains enrich them with unique physicochemical and electronic properties compared to those of the corresponding linear oligoparaphenylenes. Herein, we explore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…The distributions reveal an increase in the average value of the dihedral angles with increasing nanocage size. This is in agreement with trends previously reported for CPPs and other related bent and curved conjugated molecular systems , and is a consequence of the relaxation of the bending strain of phenylene units due to a reduction of the backbone curvature along longer phenylene bridges. It is interesting to note that the dihedral angle distributions display double peaks.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…The distributions reveal an increase in the average value of the dihedral angles with increasing nanocage size. This is in agreement with trends previously reported for CPPs and other related bent and curved conjugated molecular systems , and is a consequence of the relaxation of the bending strain of phenylene units due to a reduction of the backbone curvature along longer phenylene bridges. It is interesting to note that the dihedral angle distributions display double peaks.…”
supporting
confidence: 92%
“…Moreover, previous NEXMD simulations yield spectra and exciton migration properties in good correspondence with experimental results across a variety of conjugated molecules undergoing quite distinct exciton relaxation pathways, 35 which is very encouraging with regard to the application of the present methodology to the simulation of the photoinduced dynamics of carbon nanocages. It has been successfully applied to simulate the photoinduced dynamics of the family of [n]CPPs and other related nanohoops, 5,23,37,46 providing good agreement with more accurate quantumchemical calculations. Previous NEXMD simulations were able to associate the efficient fluorescence in large [n]CPP hoops with the exciton self-trapping due to strong vibronic coupling, breaking the Condon approximation and overriding the optical selection rules.…”
Section: ■ Computational Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…The utility and accuracy of the NEXMD development version were exemplified by its application to a variety of systems including oligomers and polymers, dendrimers, light harvesting complexes (LHCs), ,, energetic materials, and others . Additionally, our previous publications documented the development of theoretical methodology, algorithms, and analyses featured in NEXMD. ,, In this article, we outline the various functionalities of the NEXMD package derived from the development version and released for open public use and the associated getexcited.py python support package.…”
Section: Introductionmentioning
confidence: 99%
“…[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] These methods have been previously applied to simulate the photoinduced electronic energy relaxation and redistribution in CPPs and related nanohoops. 61,62 Particularly, the NEXMD (Nonadiabatic EXcited-state Molecular Dynamics) software package 44 has been extensively applied to a variety of CPPs, 5,8 and related nanohoops, 26,63 nanobelts 64 and nanocages. 65 These previous investigations have revealed that structural modifications introduced in CPPs by various substitutions and insertions induce changes in the relative efficiency of the internal conversion process involving dynamical changes of the structures such the local planarization of the chain and concomitant changes in the specific exciton spatial localization (self-trapping) 53 occurring during the excited-state dynamics.…”
Section: Introductionmentioning
confidence: 99%